Compensation strategies that influence employee retention among employees at Amanah Ikhtiar Malaysia (AIM) / Farhanim Zainal and Nurul Nabilah Patahom - Zainal, Farhanim; Patahom, Nurul Nabilah (Faculty of Business and Management, 2015)
Employee retention becomes a common issue faced by many employers in many organizations in Malaysia today. In almost all cases, the factors that affect employee retention will be different from every departments and company. The purpose of this study was to determine the dominant, relationship and level that affect employee retention. The study examined the total respondents of 132 consist of employees at Amanah Ikhtiar Malaysia (AIM). The independent variables of this study consist of the elements of compensation like salary, promotional opportunities and employee recognition. This study use non-experimental research method to find the relationship between independent variables and dependent variables which is employee retention. The researchers used questionnaire as the method to collect all the data from the respondents in accomplishing the research objectives. This study is said to be beneficial to the companies in Malaysia especially in situation where they are facing high employee turnover. It will helps them to gain awareness on the main factors and manage the issue from getting worse. Recommendations for future research are also have been discussed.